Community participation and empowerment in primary education - Govinda, R.; Diwan, Rashmi (Sage Publications, 2003)
It is recognized that community participation can play an important role in promoting primary education. This volume presents the experiences, problems encountered, and lessons learnt from initiatives launched in 5 Indian states - Madhya Pradesh, Karnataka, Rajasthan, Bihar and Kerala. It is for those involved with education and social work.